Tuning the Structure of Phosphahelicenes for Targeted Applications in Enantioselective Phosphine Organocatalysis. Issue 42 (21st June 2018) - Aillard, Paul; Gicquel, Maxime; Yavari, Keihann; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract : The use of phosphahelicenes as nucleophilic organocatalysts for [3+2] cyclization reactions between allenoates and 2‐benzylidenemalononitriles has been extended by the systematic screening of phosphines with different helical scaffolds and substitution patterns. Among others, a new series of phosphahelicenes have been prepared by bromination/Suzuki coupling reactions of a pre‐formed phosphahelicene. This late bromination approach represents a suitable strategy for accessing a broad variety of substituted phosphahelicenes from a single intermediate. It represents a powerful tool for the catalysis‐oriented optimization of their structural features. Abstract : The systematic screening of chiral phosphahelicenes as nucleophilic organocatalysts has highlighted crucial effects of both the helical backbone and substitution pattern on enantioselectivity. A late functionalization approach to the synthesis of substituted chiral phosphahelicenes allows the easy tuning of the substituents for catalyst optimization.